The Competency Gap of Early Childhood Education Teachers in Technology-Based Learning : A Digital Literacy Perspective Between Technology Use and Instructional Design - Dadan Nugraha; Gilar Gandana; Taopik Rahman (CV. Creative Tugu Pena, 2026)
This study aims to analyze the competency gap of early childhood education (ECE) teachers in technology-based learning from a digital literacy perspective, particularly between technology use and instructional design. The study employed a quantitative approach with a cross-sectional survey design involving 217 ECE teachers selected through purposive sampling. Data were collected using a Likert-scale questionnaire (1–5), which was validated using product moment correlation and tested for reliability using Cronbach’s Alpha (α = 0.964). Data were analyzed using descriptive statistics and gap analysis. The results indicate that teachers’ competencies in technology-based learning are at a moderate level (mean = 2.55). The technology use dimension shows a higher mean score (2.60) compared to instructional design (2.46), with a gap of 0.14. These findings suggest that teachers are capable of using technology in learning activities but have not yet optimally developed systematic technology-based instructional design. This gap indicates that teachers’ digital literacy remains at the operational level and has not yet progressed to higher levels involving creation and integration. The implications of this study highlight the need to strengthen teacher competencies through professional development programs emphasizing technology-based instructional design, practice-oriented training, and systemic support to enhance digital literacy comprehensively. This study contributes to the advancement of digital literacy and technology integration in early childhood education and provides a foundation for developing future teacher competency improvement models.